2023
DOI: 10.1371/journal.pone.0282246
|View full text |Cite
|
Sign up to set email alerts
|

HR LC-MS/MS metabolomic profiling of Yucca aloifolia fruit and the potential neuroprotective effect on rotenone-induced Parkinson’s disease in rats

Abstract: Yucca aloifolia L. fruit (Yucca or Spanish bayonet, family Asparagaceae) is recognized for its purplish red color reflecting its anthocyanin content, which has a powerful antioxidant activity. This study aimed to investigate yucca (YA) fruit extract’s protective effect on Parkinson’s disease (PD). In vitro study, the anti-inflammatory activity of yucca fruit extracts was explored by measuring tumor necrosis factor receptor 2 (TNF-R2) and nuclear factor kappa B (NF-KB) to choose the most effective extract. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The statistical results demonstrated that flavonoid administration [nine studies; mean difference (MD), −1.98 nmol/mg protein; 95%CI (−3.20, −0.77)] has a significant effect in reducing MDA level among the animals with cognitive impairment as the effect favors experimental/intervention group, with a heterogenicity of 87% between studies. The nine studies included are as follows: Wu et al (2012) administered green tea extract (GTex), epigallocatechin gallate (EGCG), for 7 days; Jia et al (2016) administered liquiritin for 2 weeks; Mansour et al (2017) administered 5, 7-dihydroxyflavone for 3 weeks; Peter AN and Rehab AA 2021 administered hesperidin for 8 weeks; Kwon et al (2022) administered Rhodiola sachalinensis for 3 weeks; Hawash et al (2023) administered jambolan fruit ethanolic extract for 28 days; administered baicalein for 21 days and quercetin for 42 days, respectively; and finally, Kim et al (2023) administered Sesamum indicum L. for 4 weeks.…”
Section: Malondialdehydementioning
confidence: 99%
“…The statistical results demonstrated that flavonoid administration [nine studies; mean difference (MD), −1.98 nmol/mg protein; 95%CI (−3.20, −0.77)] has a significant effect in reducing MDA level among the animals with cognitive impairment as the effect favors experimental/intervention group, with a heterogenicity of 87% between studies. The nine studies included are as follows: Wu et al (2012) administered green tea extract (GTex), epigallocatechin gallate (EGCG), for 7 days; Jia et al (2016) administered liquiritin for 2 weeks; Mansour et al (2017) administered 5, 7-dihydroxyflavone for 3 weeks; Peter AN and Rehab AA 2021 administered hesperidin for 8 weeks; Kwon et al (2022) administered Rhodiola sachalinensis for 3 weeks; Hawash et al (2023) administered jambolan fruit ethanolic extract for 28 days; administered baicalein for 21 days and quercetin for 42 days, respectively; and finally, Kim et al (2023) administered Sesamum indicum L. for 4 weeks.…”
Section: Malondialdehydementioning
confidence: 99%
“…After being trained, three different trials/day for each rat were performed using the rotarod’s accelerating speed mode (4 to 40 rpm) for 5 min. The latency to fall off the rotarod was recorded, and the results were expressed as mean of three trials for each rat [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The experiment was video-recorded and analyzed by the observer. Activity (swimming and climbing times) and immobility times were the parameters measured in this test and were considered an index for depression [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latency to fall from the apparatus was recorded, and the mean of the three trials was calculated for each rat. Rats that stayed on the drum for 300 s without falling were removed, and their time was scored as 300 s. The apparatus was properly cleaned with a 70% ethanol solution before each trial [22,23].…”
Section: Rota Rod Testmentioning
confidence: 99%